2021
DOI: 10.3390/land10060629
|View full text |Cite
|
Sign up to set email alerts
|

Fit for Purpose Land Administration: Country Implementation Strategy for Addressing Uganda’s Land Tenure Security Problems

Abstract: The Republic of Uganda is one of the five countries within the East African region. Uganda’s efforts to increase land productivity are hampered by land tenure insecurity related problems. For more than ten years, Fit for Purpose Land Administration (FFPLA) pilot projects have been implemented in various parts of the country. Uganda is now in advanced stages of developing a country strategy for implementing a fit for purpose approach to land administration, to define the interventions, time and cost required to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The approach strives to achieve a flexible, inclusive, participatory, affordable, reliable, attainable, and upgradeable land administration system through the key principles of the fundamental framework. Several studies agree with the benefits of the FFPLA for ensuring tenure security in a short period and at a reasonable cost [10,42].…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…The approach strives to achieve a flexible, inclusive, participatory, affordable, reliable, attainable, and upgradeable land administration system through the key principles of the fundamental framework. Several studies agree with the benefits of the FFPLA for ensuring tenure security in a short period and at a reasonable cost [10,42].…”
Section: Resultssupporting
confidence: 55%
“…4.1.2. Assessing Suitability of the FFPLA Spatial, Legal, and Institutional Frameworks Musinguzi et al [42] investigated three FFPLA pilot programs in different parts of Uganda and highlighted spatial, legal, and institutional framework gaps for transforming the present Western-style land management system into an efficient FFPLA. The study identified promising practices from the pilot implementations.…”
Section: Ffpla Improving the Existing Tenure Security Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Musinguzi et al [30] explore, in great depth, the process of developing a national strategy for providing secure land rights at scale in Uganda, covering 23 million land parcels. They describe the current tenure types in Uganda and examine three representative pilot projects, in order to identify how lessons learned from these case studies informed a FFPLA implementation strategy in terms of building the spatial, legal and institutional frameworks.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…This is because such areas usually have abundant land which may seem to policy makers as redundant and thus more likely to be sources of land give away to investors. [58] noted that land based investments are attracted to areas of low population density, low educated leaders and land availability. A study by [36] find that Nakasongola and Nwoya had more land access and comparatively lower percentages of educated adults.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%